2021
DOI: 10.3390/nu13061850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High-Intensity Dietary Intervention on Changes in Dietary Intake and Eating Pathology during a Multicomponent Adolescent Obesity Intervention

Abstract: Concerns remain about dietary changes during pediatric obesity treatment and eating pathology, which have not been investigated. This secondary data analysis from a randomized clinical trial examined associations between adolescents’ changes in energy intake and diet quality during obesity treatment with post-treatment eating pathology. Adolescents (N = 82: 13.7 ± 1.2 y, 34.9 ± 7.0 kg/m2, 63.4% female, 46.3% black) received TEENS+, a 4-month multicomponent intervention. TEENS+ provided individualized dietary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Higher baseline dietary restraint scores in obese children have been associated with increased rates of premature drop out from the intervention program compared to children who completed the program, independent of gender, age, and BMI z-score at baseline and mother's education level [73]. On the other hand, in a secondary analysis of an RCT focusing on changes in energy intake and diet quality during obesity treatment with post-treatment eating pathology in adolescents, there was no association between intensity of diet and EDs [74]. In a systematic review, current measures of dietary restraint and dieting are not associated with ED risk in the short term; however, long-term data are limited [75].…”
Section: Managementmentioning
confidence: 97%
“…Higher baseline dietary restraint scores in obese children have been associated with increased rates of premature drop out from the intervention program compared to children who completed the program, independent of gender, age, and BMI z-score at baseline and mother's education level [73]. On the other hand, in a secondary analysis of an RCT focusing on changes in energy intake and diet quality during obesity treatment with post-treatment eating pathology in adolescents, there was no association between intensity of diet and EDs [74]. In a systematic review, current measures of dietary restraint and dieting are not associated with ED risk in the short term; however, long-term data are limited [75].…”
Section: Managementmentioning
confidence: 97%
“…This finding is important given the concerns that TLE may lead to unhealthy eating behaviors and attitudes. Disordered eating behaviors are prevalent among adolescents with obesity; however, many studies have suggested that monitored intervention programs implemented by trained professionals may decrease eating behavior symptomatology [82][83][84]. The potential for unhealthy eating should be continuously monitored in future studies [73,83,85].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary guidance provided in TEENS+ was designed to reduce adolescents’ daily caloric intake and improve dietary quality by adding low-calorie, nutrient-dense foods (“Go Foods”), and reducing energy-dense, nutrient-poor foods [ 18 , 19 , 26 , 27 ]. At the start of treatment, adolescents were prescribed a daily calorie range (1200–1400 kcal/day for girls; 1500–1800 kcal/day for boys) and a Go-Food goal (# Go-Foods/day), designed to result in a 1–2 lb weight loss each week.…”
Section: Methodsmentioning
confidence: 99%
“…Data were from the TEENS+ intervention during which adolescents participated in a 4-month behavioral weight loss treatment. Previous reports from this study showed that adolescents in TEENS+ decreased their energy intake, improved their diet quality, and experienced significant reductions in BMI post-treatment [18,19]. The aims of this secondary analysis were to quantify changes in (1) the home food environment, (2) dietary quality, (3) daily energy intake, and (4) BMI from baseline to post-treatment by household food security status.…”
Section: Introductionmentioning
confidence: 98%